(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article explores the integration of BIM technologies in English language instruction for construction and architecture students, highlighting enhanced vocabulary acquisition, technical communication skills, and interdisciplinary learning. BIM tools facilitate immersive, project-based activities that contextualize English terminology in real-world scenarios, bridging linguistic and professional competencies. Empirical insights from case studies demonstrate improved engagement and proficiency.